The proportion of infectious disease cases, its associated factors, and the appropriateness of antimicrobial prescription among Rohingya refugee pediatric patients in IMARET mobile clinics - Mohamed Tahir, Ahmad Rashidi; Ee, Xuan Wen; Abdul Rashid, Aneesa; Yahaya, Ahmad Yusuf; Devaraj, Navin Kumar (Springer, 2021)
The Rohingyas fled from their home to escape ethnic persecution. Due to their status as refugees they have difficulties in accessing healthcare leading to avoidable mortality and morbidity. Infectious diseases are reported to be among the causes. To ease access to healthcare, IMAM Response and Relief Team (IMARET) provides a free monthly clinic for them. The objective of this study is to determine the proportion of infectious diseases and appropriateness of antimicrobial usage among its pediatrics patients. It was conducted in 2017, through universal sampling. Information retrieved were via interviews and medical records. The majority diagnosis were infectious diseases (57.1%), which include respiratory infections (77.3%), skin (13.6%), gastrointestinal (4.5%), eye and ear infection (both 1%). Albendazole (40.7%) was the most prescribed. Only 7.4% were appropriately prescribed antimicrobials. Age (p = 0.005) and BMI (p = 0.006) were significantly associated with infections.